Od ludu wybranego do narodu cierpiącego, wygnanego, tułaczego. Komplementarność motywów w literaturze staroserbskiej - Lis-Wielgosz, Izabela (Przegląd Wschodnioeuropejski, 2018)
The paper regards a problem of realization and function of the motifs of emigration and wandering that occur in a complementary arrangement in Old Serbian literature. They consist of a specific scheme of presentation and exegesis concerning the historical, religious and cultural reality. The motifs are a characteristic strategy of the expression of collective fate – the tragic experience of the Great Exodus in 1690. They find an extraordinary realization in brief literary form – the notations wherein the motifs establish a definite semantic collection, combined with many already consolidated ideas and ideological constructions. That collection is to met with a favourable response of the subsequent cultural phenomena and conceptions, creating a unique image of the Serbian community. Those phenomena constitute a sort of topic structure, based on the already established imaginative conceptions, especially the messianic image of the “chosen nation” and “nation-martyr” that create a new character of the Serbian community, or make the previous one concrete, henceforth described not only in the categories of election and martyrdom, but also of “emigration from the Turkish land”, wandering and homelessness in the land of Hungary.